2007
DOI: 10.1007/s11242-007-9179-3
|View full text |Cite
|
Sign up to set email alerts
|

Wetting Phase Bridges Establish Capillary Continuity Across Open Fractures and Increase Oil Recovery in Mixed-Wet Fractured Chalk

Abstract: The effect of fractures on oil recovery and in situ saturation development in fractured chalk has been determined at near neutral wettability conditions. Fluid saturation development was monitored both in the matrix and in the fractures and the mechanisms of fracture crossing were determined using high spatial resolution MRI. Capillary continuity across open oil-filled fractures was verified by imaging the water bridges established within the fracture. Despite an alternate escape fracture for the water, separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…The pores in our chalk samples are 戏100 times smaller than sandstone (24), but their randomly distributed, variable size hydrophobic and hydrophilic patches put them decidedly into the fractionally wet class. For macroscopic determination by imbibition, the sample would appear water-wet, which is consistent with macroscopic data from our own samples and those of others (25); water imbibes easily into freshly fractured chalk surfaces.…”
Section: Afm Force Mappingsupporting
confidence: 91%
“…The pores in our chalk samples are 戏100 times smaller than sandstone (24), but their randomly distributed, variable size hydrophobic and hydrophilic patches put them decidedly into the fractionally wet class. For macroscopic determination by imbibition, the sample would appear water-wet, which is consistent with macroscopic data from our own samples and those of others (25); water imbibes easily into freshly fractured chalk surfaces.…”
Section: Afm Force Mappingsupporting
confidence: 91%
“…Previous work have discussed MRI imaging for core characterization purposes (Baldwin and Spinler, 1998;Baldwin and King, 1999), the monitoring of imbibition and displacement processes (Baldwin, 1999) and the application of MRI to the study of formation damage. Recent studies have reported flow behavior and production mechanisms in fractured chalk and their dependency of wettability, rate and fracture aperture and fracture configurations (Graue et al, 2001;Aspenes et al, 2002;Aspenes et al, 2008).…”
Section: The Core Scalementioning
confidence: 99%
“…A good understanding of transport phenomena in unsaturated fractured porous media is the key to the successful description of a number of industrial 2 processes such as oil recovery from petroleum reservoirs [1][2][3], water resources and waste disposal management [4,5], and wicking of liquids connected to porous materials in printing or coating processes as well as cleaning applications [6,7]. For instance, Ghezzehei and Or [4] developed a theoretical model for liquid fragmentation along inclined fractures and then Or and Ghezzehei [5] applied this model to study the potential for more rapid arrival times of pollutants carried with discrete liquid elements along the inclined fractures compared to continuum liquid film flow on both fracture walls.…”
Section: Introductionmentioning
confidence: 99%
“…A formula for the critical aperture was suggested by Sajjadian et al [14]. Aspenes et al [1] experimentally showed that wetting phase bridges stabilize capillary continuity across open fractures and increase oil recovery. They discussed that the size of the bridges seems controlled by the wettability of the rock and not by the differential pressure applied across the open fractures.…”
Section: Introductionmentioning
confidence: 99%